Contributions to Nephrology 2005
DOI: 10.1159/000086043
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 47 and Renal Fibrogenesis

Abstract: Recent research has greatly increased our knowledge regarding the molecular mechanisms of collagen synthesis and processing. Heat specific shock protein (HSP47) is a collagen-specific molecular chaperone, and helps in post-translational modifications of procollagens, during biosynthesis of collagen. Both in vivo and in vitro studies have convincingly demonstrated that HSP47 is localized in the endoplasmic reticulum of collagen-producing cells, and that its synthesis is closely associated with the rate of proco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Previous in vivo and in vitro studies have convincingly shown that HSP47 plays an important role in the onset and progression of various fibrotic diseases, particularly those affecting the artery wall (24). HSP47 is localized in the endoplasmic reticulum of collagen-producing cells and is thought to be essential for the synthesis, processing, and secretion of pro-collagen molecules (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo and in vitro studies have convincingly shown that HSP47 plays an important role in the onset and progression of various fibrotic diseases, particularly those affecting the artery wall (24). HSP47 is localized in the endoplasmic reticulum of collagen-producing cells and is thought to be essential for the synthesis, processing, and secretion of pro-collagen molecules (17).…”
Section: Discussionmentioning
confidence: 99%
“…6 During this process tubule cells loose epithelial features and convert to fibroblast-like cells. 3 This epithelial-mesenchymal transition (EMT) is paralleled for example by the expression of fibroblast-specific protein-1(FSP1), 13 heat shock protein 47 (HSP 47) 10,16,21 and a-smooth muscle actin (SMA). 31 In contrast, mesenchymal-epithelial transition (MET) plays an important role, when stem/progenitor cells are applied to support regeneration in acute or chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…TGF- β 1 is the core cytokine leading to the synthesis of ECM, which is responsible for mesangial fibrosis and hypertrophy under diabetic conditions [6]. The major components of the ECM proteins collagen types I–IV and their synthesis and immoderate deposition are consistently observed in multifarious renal disease processes affecting humans and experimental animals [7, 8]. …”
Section: Introductionmentioning
confidence: 99%